2023
DOI: 10.3390/brainsci13071074
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Gain in Digital Foreign Language Learning

Abstract: This systematic review examines the potential of digital language learning in contributing to students’ cognitive gains. The study reviews existing research on the relationship between digital language learning and cognitive benefits, with a focus on enhanced problem-solving skills, memory, and multitasking ability. The research questions explored in this study are (1) does digital language learning contribute to cognitive gains in foreign language education? and (2) what are the pedagogical implications for c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…So far, there has been a variety of research on the use of technology in education in general and in language education in specific. Klimova (2023) has conducted a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology to identify and analyze relevant research articles and found that cognitive gains are believed to be more effective when working with printed texts as learners are frequently exposed to more senses through digital language education. This was confirmed by another study by Klimova and Kacetl (2017), who announced the high ability of vocabulary acquisition, more engagement opportunities, and students' inclusion in communication in computer games.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So far, there has been a variety of research on the use of technology in education in general and in language education in specific. Klimova (2023) has conducted a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology to identify and analyze relevant research articles and found that cognitive gains are believed to be more effective when working with printed texts as learners are frequently exposed to more senses through digital language education. This was confirmed by another study by Klimova and Kacetl (2017), who announced the high ability of vocabulary acquisition, more engagement opportunities, and students' inclusion in communication in computer games.…”
Section: Literature Reviewmentioning
confidence: 99%